Educação e empreendedorismo: reflexões associadas ao fazer docente na contemporaneidade - Nascimento, Belmiro José da Cunda (2020)
In the context of cyberculture, it is imperative a movement of (re) meaning of the postures of teachers, who no longer partially meet or meet, the demands arising from a new social and cultural organization. We observed in our daily lives of trainers of future teachers an emergency of valuing technological training, in a priority way, seeking the elaboration of new educational models that meet the contingencies demanded by the hybrid organization ( in person and virtual) of school spaces. In a world without guarantees, where standard discourses no longer apply in which there is no longer a right and common north for all people; where references have been lost in the things where we have and we need to abandon the idea that our action can be based on a guarantor reason (a last foundation), entrepreneurial education and teacher training contain some mismatch of ideas and concepts about how we have to teach or educate teachers to be entrepreneurs.In this perspective, this thesis is a contribution to the studies of ideas about pedagogy that we deepen to specifically produce the challenge of drawing reflections and clues to identify instrumental, technological and curricular formative actions to form a pedagogically entrepreneurial teacher. i analyze, initially, the context and locus within the theme, the discourses, characterizing the pedagogical-ideological positioning that other researchers had already been announcing. there is a privilege from the perspective of pedagogy as a promoter of changes in teaching making without signaling entrepreneurship as a pedagogical practice incorporated into methodology. a second moment, of the thesis, addresses the extensions of other voices that preceded this work through related studies and trends referring to the context of entrepreneurship in education, but reproducing the echo associated with the world of business and finance, practices that are still based on the technical-utilitarian territory on the vast continent of established and legitimized conventions in academia. finally, from the analysis of focus groups and participants' perceptions, although in the nascent pedagogy gradually assumes, leadership in conducting a new method, i analyze perceptions sensitive to the variability of the context of cyberculture in which teachers individually react in different pedagogical forms in their teaching making, which makes it increasingly essential, but not discussed, the complexity of today and the experiences that impose a methodological deviation.It is no longer possible to think of pedagogy in an application or even normative adaptation of a knowledge produced at a period or moment of a world built with guarantees, in which the standard discourses where there is a right and common north for all people; where references to the things where we have and need, we adopt the idea that our action can be based on a guarantor reason (a last foundation). In this thesis, teachers do not fear affirming that education as a world of teaching learning, considering pedagogy as a method is not here to be known and recognized, but in the face of cyberculture and the complexity of reality, is to be built in an unceasing trial. This is a conclusion of this thesis. We can form an entrepreneurial teacher, we can expand experiences, but this will only tell us representations, the need for a creative curriculum foundation. We need more research and future work to continue on behalf of our students, accessing a world, which from the perspective of cyberculture is mobile, inaccurate and therefore unpredictable and therefore an entrepreneurial pedagogy has a sense of Urgency. It was from this perspective that we went to research: Is it possible to train an entrepreneurial teacher? What training, instrumental and technological actions should be considered to train an entrepreneurial teacher with regard to pedagogical aspects? Keywords: Entrepreneurial Education. Teacher Education. Entrepreneurship.